Jestem twój - CZOP, IRENEUSZ (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2016)
I’m yours The author analyses in detail the structure of the leading role based on the film “I’m yours” His analysis takes into account acting skills, the relations between the protagonists and adversaries and also cinematic time and space. He appreciates the role played by the screenwriter and establishes the principles for cooperation between actors and the director.